2014 Fourth International Conference on Digital Information and Communication Technology and Its Applications (DICTAP) 2014
DOI: 10.1109/dictap.2014.6821723
|View full text |Cite
|
Sign up to set email alerts
|

Finger-spelling recognition system using fuzzy finger shape and hand appearance features

Abstract: In this paper, we introduce a method for fingerspelling recognition system. The objective is to help the deaf or non-vocal persons to improve their skills on the finger-spelling. Many researches in this field have proposed methods mostly based on hand posture estimation techniques. We propose an alternative flexible method based on fuzzy finger shape and hand appearance analysis. By using depth image, the hand is extracted and tracked using an active contour like method. Its features, such as, finger shape, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Generally, there are three levels of sign language recognition: finger spelling (alphabets), isolated sign gestures and continuous sign gestures. For finger spelling, the number of hand motions is very small and sometimes mainly finger configuration and orientation information are included [ 30 , 31 , 32 ]. For isolated sign gestures, usually features that characterize whole hand location and movement as well as appearance features that result from hand shape and orientation are extracted [ 3 , 13 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are three levels of sign language recognition: finger spelling (alphabets), isolated sign gestures and continuous sign gestures. For finger spelling, the number of hand motions is very small and sometimes mainly finger configuration and orientation information are included [ 30 , 31 , 32 ]. For isolated sign gestures, usually features that characterize whole hand location and movement as well as appearance features that result from hand shape and orientation are extracted [ 3 , 13 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contour tracking uses deformable contours or snakes to track regions over consecutive frames. For example, a nger spelling detector is developed using this technique in [13] .…”
Section: Trackingmentioning
confidence: 99%
“…13 shows the confusion matrix. Looking at the main diagonal of that table, it can be observed that the performance of many of the gestures is more than an 80% indicating also a stable performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation